P951 Intraprocedural echocardiographic technique to locate the insertion points of artificial chordae during transventricular beating heart mitral valve repair: ultrasound ""starry sky"". (17th January 2020) - Vairo, A; Marro, M; Speziali, G; Rinaldi, M; Salizzoni, S
Abstract: BACKGROUND: Mitral valve repair is the preferred surgical treatment for severe mitral regurgitation due to degenerative leaflet prolapse. Within the growing era of transcatheter treatments for valvular heart disease, an innovative micro-invasive trans-ventricular beating-heart procedure was developed. Three-dimensional transoesophageal echocardiographic guidance is crucial to assist the operator in instrument navigation and chords positioning. Indeed, it is important an equidistant chords placement on the leaflet to ensure a uniform force distribution on the prolapsing segment and to avoid damaging of the previously inserted chords. PURPOSE: To propose an intraoperative three-dimensional echocardiographic technique that allows operators to see the exact location of the polytetrafluoroethylene (ePTFE) chords used for the mitral repair. METHODS: The procedure is performed using a device that is introduced through a posterolateral ventriculotomy and it is advanced towards the mitral valve under real-time 3D transoesophageal guidance. The prolapsing segments are grasped with the jaw of the instrument and the chords are implanted to achieve the proper distribution of forces and then tensioned and secured outside the ventricle. The proposed technique exploits the greater echogenicity of the artificial chord loop compared to native chords and leaflets. By lowering of the gains, remaining in the three-dimensional mitral valve surgical view, the signals of the native structures are attenuated, the underlying ventricular cavity appears black and the insertion points are visible as an intense signal on the virtual free edge of the leaflet treated. Figure 1 shows the intraoperative sequence of images of a case performed at our centre. The images were acquired using real time single beat three-dimensional reconstruction. Figure 1A shows the surgical view of the native valve with prolapse of the P2-P3 scallops. Image 1B reveals the prolapsing leaflet grasping and device location. After gain lowering, it's possible to see the intense signal of the positioned artificial chord (Figure 1C). It can also be noted how this position matches with the position of the device at the time of grasping. Image 1D shows the partial disappearance of the prolapse during the tensioning test after the positioning of a second chord in a more medial position. Figure 1E shows the correct position of the ePTFE chords. We can notice the second chord placed in a medial position from the first one. This view, with dark ventricular chamber and intense signals of chordae loops, looks like a "STARRY SKY". RESULTS: This technique allows to locate the correct insertion points of the artificial chords during the procedure. CONCLUSIONS: This is a simple technique to guide operators during trans-ventricular beating heart mitral valve repair with ePTFE chords.